Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/ijms19092843
|View full text |Cite
|
Sign up to set email alerts
|

Aloe Genus Plants: From Farm to Food Applications and Phytopharmacotherapy

Abstract: Aloe genus plants, distributed in Old World, are widely known and have been used for centuries as topical and oral therapeutic agents due to their health, beauty, medicinal, and skin care properties. Among the well-investigated Aloe species are A. arborescens, A. barbadensis, A. ferox, and A. vera. Today, they account among the most economically important medicinal plants and are commonly used in primary health treatment, where they play a pivotal role in the treatment of various types of diseases via the modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
101
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(113 citation statements)
references
References 272 publications
(314 reference statements)
1
101
0
4
Order By: Relevance
“…In the present study, the leaf latex and the TLC fractions of A. adigratana showed a broad-spectrum antimicrobial activity. is finding is in line with previous works that indicated that most Aloe species possessed antimicrobial activities [22]. In both Gram-positive and Gram-negative bacterial strains, the clinical isolate strains were more resistant than the reference strains to the positive control (ceftriaxone) and all tested samples.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the leaf latex and the TLC fractions of A. adigratana showed a broad-spectrum antimicrobial activity. is finding is in line with previous works that indicated that most Aloe species possessed antimicrobial activities [22]. In both Gram-positive and Gram-negative bacterial strains, the clinical isolate strains were more resistant than the reference strains to the positive control (ceftriaxone) and all tested samples.…”
Section: Resultssupporting
confidence: 92%
“…Several of these endemic species possessed different biological activities, including antimicrobial [9,10], antitrypanosomiasis [11], antileishmaniasis [12,13], antimalarial [14][15][16], wound healing [17], anti-inflammatory [17,18], anticancer [19], antidiabetic [20], and antioxidant activities [21]. is relevance indicates that Aloe is the store house of numerous bioactive compounds [22]. e experimental plant A. adigratana (Figure 1), locally known as "eret" in Amharic and "ere habesha" in Tigrigna, is one of the endemic Aloe species in Ethiopia which is specifically found in Adigrat, Tigray region [23].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional medicines or herbal remedies and their derivatives have been extensively used as complementary agents in cancer treatment (Safarzadeh, Sandoghchian Shotorbani, & Baradaran, ; Salehi et al, ; Salehi et al, ; Salehi et al, ; Salehi et al, ). Among the various phytochemicals with anticancer effects, silymarin is one of the highly potent antioxidant agents, with some other biochemical activities, including its positive effects in both cancer prevention and treatment, broadly confirmed through numerous studies (Ramasamy & Agarwal, ).…”
Section: Introductionmentioning
confidence: 99%
“…В этом плане большой интерес вызывают суккулентные растения рода Aloe, включающего более 500 видов, для которых характерно формирование водозапасающих листьев. В обзоре [1] представлены данные об использовании различных видов Aloe в медицине, пищевой и косметической индустрии. Наиболее исследованными и используемыми видами Aloe являются A. arborescens Mill., A. ferox Mill.…”
Section: Introductionunclassified
“…и A. vera (L.) Burm. f. [1]. Ранее был проведен скрининг 15 видов Aloe по оценке антиоксидантной активности (АОА) их экстрактов амперометрическим и хемилюминесцентным методами [2].…”
Section: Introductionunclassified